STRATEGI KOMUNIKASI DINAS KESEHATAN DALAM PENANGANAN COVID 19 KEPADA MASYARAKAT DI KABUPATEN KUANTAN SINGINGI - Wirasti, Revia; Firdaus, Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Coronavirus disease 2019 or covid 19 is a new type of disease caused by a virus from the coronavirus group, namely the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This virus has spread throughout the country, including Kuantan Singingi Regency. The purpose of this study was to determine the communication strategy of the Kuantan Singingi District Health Office in implementing performance for the management and prevention of Covid 19. The researchers conducted an investigation at the District Health Office of Kuantan Singingi because Kuantan Singingi Regency was originally a green zone and After the first case was found, the community continued to carry out normal activities until Kuantan Singingi Regency was confirmed as a red zone in Riau province. The Kuantan Singingi Regency Health Office as an institution that manages Covid 19 in the Kuantan Singingi Regency has a strategy that researchers find interesting in their prevention steps and that makes researchers interested in conducting research.This study uses a qualitative descriptive method with strategic communication theory. The research subject determination technique used intentional and accidental sampling techniques. The informants in this study were 5 people. The data collection techniques used were observation, interviews, and documentation. The data analysis techniques in this study used Miles and Huberman interactive data analysis techniques that consisted of data reduction, data presentation, and drawing conclusions or verification. To achieve data validity in this study, the researchers used extension of participation and triangulation.The result of this research is that the communicator's strategy is the Kuantan Singingi Regency Health Office with the criteria that people consider themselves communicative, have high credibility, have experience, can be trusted and update the development of covid 19. The Audience strategy These are all the people at Kuantan Singingi Regency, especially those who are over 40 years old and already have a history of illness. The communication messages transmitted are in the form of informative messages (notifying the dangers of covid 19), persuasive (inviting to comply with health protocols) and coercive (penalties for collecting garbage at the places of raids). The media used are print media (banners, billboards and posters), electronic media (Kuansing FM radio), digital media (videotron), online media (website dinkes.kuansing.go.id) and social media (instagram @dinkeskuansing and facebook Kuansing Health Office).